Chemoreactive Natural Products that Afford Resistance Against Disparate Antibiotics and Toxins. Issue 13 (1st March 2016) - Du, Lin; You, Jianlan; Nicholas, Kenneth M.; Cichewicz, Robert H.
Abstract: Microorganisms use chemical inactivation strategies to circumvent toxicity caused by many types of antibiotics. Yet in all reported cases, this approach is limited to enzymatically facilitated mechanisms that each target narrow ranges of chemically related scaffolds. The fungus‐derived shikimate analogues, pericoxide and pericosine A, were identified as chemoreactive natural products that attenuate the antagonistic effects of several synthetic and naturally derived antifungal agents. Experimental and computational studies suggest that pericoxide and pericosine A readily react via SN 2′ mechanisms against a variety of nucleophilic substances under both in vitro aqueous and in situ co‐culture conditions. Many of the substitution products from this reaction were highly stable and exhibited diminished toxicities against environmental fungal isolates, including the Tolypocladium sp. strain that produced pericoxide and pericosine A. Abstract : Electrophilic warheads : Fungus‐derived shikimate analogues, pericoxide and pericosine A (see picture; blue), have been identified as archetypal chemoreactive natural products that neutralize the antagonistic properties of chemically diverse synthetic and naturally derived antifungal agents and toxins (see picture; left).